Стійкість до модельованого водного стресу R2 рослин тютюну, отриманих у результаті клітинної селекції з іонами важких металів - Сергєєва, Лариса; Броннікова, Лариса; Sergeeva, Larisa; Bronnikova, Larisa (Східноєвропейський національний університет імені Лесі Українки, 2016)
Методом клітинної селекції із використанням катіонів Cd2+ отримано клітинні лінії й рослини R0, R1, R2 тютюну. Усі рослинні форми відзначалися стійкістю до летальних водних стресів. Стійкість варіантів була коорди- нована з підвищеним рівнем вільного проліну, який змінювався залежно від величини стресового тиску. Осмос- тійкість варіантів є генетично обумовленою ознакою. The cell selection with heavy metal ions for obtaining plant forms, resistant to abiotic stresses is advisable. Especially it is recommended to use cadmium cations for obtaining variants, resistant to water deficit. On selective media with the addition of lethal for cell cultivars doses of Cd2+ cations resistant tobacco cell lines occurred. Regenerants R0 and seed progenies R1, R2 were obtained from those lines. Cell lines and R0 and R1 plants challenged the water stress that was established by mannitol addition. Variants resistance was combined with high level of free proline. The investigation of R2 plants resistance levels and their proline status were the objects of the research. Young R2 plants (~ 10,0 cm length) were tested in liquid nutrition solution with the addition of 0,3 M mannitol during 5 days. Such stress pressure was lethal for wild type plants. The leaf free proline level at 5-th day of experiment exceeded normal parameter at ~ 3 times. At 5-th day cultural conditions were changed and plants were divided. Some plants were returned to normal condition the others were moved to solution with higher osmotic stress pressure (0,6 M mannitol). R2 plants actively adapted to both conditions and maintained viability. At second day after resettlement the plans free proline levels decreased in comparison with parameters that were marked before this procedure. There was predicted that this phenomenon was the result of alternative compatible solution (sucrose) accumulation.
The Resistance to Simulated Water Stress of R2 Tobacco Plants Obtained Via Cell Selection With Heavy Metal Ions
Keywords: tobacco; proline; tolerance; water deficit; cadmium cations; cell selection; тютюн; пролін; водний дефіцит; стійкість; клітинна селекція; катіони кадмію